The Impact of Applying Wordwall as a Learning Media for 8th-Graders' Vocabulary Mastery - Hilyatuts Tsaniyah; Rahayu Kuswardani (Pedagogi: Jurnal Ilmiah Pendidikan, 2026)
This study was conducted with the aim of testing the impact of applying Wordwall as a learning media on eighth-grade students’ vocabulary mastery, particularly on action verbs and temporal conjunctions in procedure texts. The research design used in this study was a quasi-experimental design involving 50 eighth-grade students. The data were collected using a vocabulary test as a research instrument. The instrument was validated by experts and tested for reliability before administering to the experimental and control classes. The data were collected through six meetings. Four of the meetings were used to give treatment using Wordwall in the experimental class, while the control class was taught using the students’ handbook. The data were analyzed through some steps and using an Independent Sample T-Test for hypothesis testing. The findings of this study showed that the students in the experimental class experienced a significant improvement in their vocabulary mastery after learning vocabulary using Wordwall. The t-test results indicated that there was a significant difference between the post-test scores of both classes (p < 0.05) with an effect size of 0.644, indicating a large effect. Therefore, the use of Wordwall has a positive impact on improving eighth-grade students' vocabulary mastery.